Determination of transportation service quality factors for university campuses: evidence from bus service quality in Yildiz Technical University - Koc, Kerim; Kaya, Hasan Alper (YILDIZ TECHNICAL UNIV, 2021)
Managing service quality is an important element in customer satisfaction and loyalty for any business organization. Even though service quality in public transportation systems has widely been investigated, service quality inside university campuses is overlooked in the literature. To fill this gap, this study aims to determine factors affecting quality of public transportation service for students, staff, and academic personnel inside the university campuses. 30 service quality elements were determined through an in-depth literature review, accompanied by a focus group discussion. A questionnaire survey was designed, and 472 secured responses were attained from public transportation users in Yildiz Technical University Davutpasa Campus (YTUDC). Then, collected data were analysed by adopting both SERVQUAL and SERVPERF approaches. According to the results of exploratory factor analysis, seven factors were determined as; responsiveness, courtesy, punctuality (service), information accessibility, tangibles, occupancy, and security. Independent sample t-test was also conducted to explore perception differences between female and male users. The results indicate that female respondents have experienced better performance related to appearance of the bus drivers, while male users have experienced better performance related to passenger safety in the bus. The findings can be regarded as a tool to develop a policy promoting sustainable public transportation service in university campuses.
Keywords: Campus bus service; Factor analysis; Service quality; SERVQUAL; SERVPERF; CUSTOMER SATISFACTION; CONSTRUCTION WASTE; LOYALTY; PERCEPTIONS; IMPACT; SCALE; Engineering